Community entrepreneurship. From genesis to legitimization - Buratti, Nicoletta; Albanese, Massimo (Piccola Impresa / Small Business, 2023)
Purpose. Community Entrepreneurship (CE) at its very origin has been associated with the process of building a robust, entrepreneurial community, as a social as well as an economic endeavor by community entrepreneurs. Since then, many experiences have emerged all around the world, in impoverished territories of the Global North as well as in depleted contexts of the Global South, often giving birth to a specific kind of enterprise, named Community-based Enterprise or simply Community Enterprise. Apart from the framework of Community Entrepreneurship, these initiatives have often been explored under the social entrepreneurship construct, with which it shares many similarities. However, CE presents some distinctive features that may advocate a specific role within entrepreneurship studies. Considering the above, our study aims to provide an extensive background of issues related to CE, focusing on its specificities as well as its relationships with other strands of entrepreneurship studies. Design/methodology/approach. A systematic literature review on Scopus and Web of Science Core Collection (WoS) has been carried out, limiting it to peer-reviewed academic articles published in English between 1990 and 2022. Findings. Beyond descriptive analytics, the results discuss the main research topics explored within the realm of CE, highlighting challenges that connect researchers and practitioners. Practical and Social Implications. Considering that both community enterprises and other kinds of Community Entrepreneurship are relevant for the development and regeneration of depleted contexts, especially in rural areas, this analysis can support practitioners and policy-makers willing to foster entrepreneurial initiatives based on local community involvement. Originality of the study. Although the literature on CE dates back to the 1990s, it has recently experienced renewed interest from scholars. However, no systematic literature reviews on this topic have been already developed.